ATTITUDES AND ACCEPTANCE TOWARD THE TECHNOLOGY OF CRYONICS IN GERMANY. (5th February 2014) - Kaiser, Stephanie; Gross, Dominik; Lohmeier, Jens; Rosentreter, Michael; Raschke, Jürgen
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: This study explores the awareness and the degree of acceptance of the idea of the medical technology cryonics—the freezing of a corpse to revive it in the future—among German citizens. Methods: Data were collected on the basis of a representatively weighted online survey of 1, 000 people aged between 16 and 69 years and resident in the Federal Republic of Germany. Results: Forty-seven percent stated that they had already heard of cryonics; 22 percent could imagine having their bodies cryonized after their deaths. For 53 percent, participation in the latest technological developments which correlated with the approval of the conceivability of cryopreservation was important. The majority of the respondents were not skeptical or cautious about innovations in the medical field. Conclusions: The study shows that cryonics is known and accepted to a certain extent. However, a large proportion of respondents did not believe that it was desirable to use medical technology to overcome death, and fundamentally rejected a post-mortal continuation of life.